Controlling the Surface Functionalization of Ultrasmall Gold Nanoparticles by Sequence‐Defined Macromolecules. Issue 4 (15th December 2020) - van der Meer, Selina Beatrice; Seiler, Theresa; Buchmann, Christin; Partalidou, Georgia; Boden, Sophia; Loza, Kateryna; Heggen, Marc; Linders, Jürgen; Prymak, Oleg; Oliveira, Cristiano L. P.; Hartmann, Laura; Epple, Matthias
Abstract: Ultrasmall gold nanoparticles (diameter about 2 nm) were surface‐functionalized with cysteine‐carrying precision macromolecules. These consisted of sequence‐defined oligo(amidoamine)s (OAAs) with either two or six cysteine molecules for binding to the gold surface and either with or without a PEG chain (3400 Da). They were characterized by 1 H NMR spectroscopy, 1 H NMR diffusion‐ordered spectroscopy (DOSY), small‐angle X‐ray scattering (SAXS), and high‐resolution transmission electron microscopy. The number of precision macromolecules per nanoparticle was determined after fluorescent labeling by UV spectroscopy and also by quantitative 1 H NMR spectroscopy. Each nanoparticle carried between 40 and 100 OAA ligands, depending on the number of cysteine units per OAA. The footprint of each ligand was about 0.074 nm 2 per cysteine molecule. OAAs are well suited to stabilize ultrasmall gold nanoparticles by selective surface conjugation and can be used to selectively cover their surface. The presence of the PEG chain considerably increased the hydrodynamic diameter of both dissolved macromolecules and macromolecule‐conjugated gold nanoparticles. Abstract : Ultrasmall gold nanoparticles (diameter about 2 nm) were surface‐functionalized with cysteine‐carrying precision macromolecules. These consisted of sequence‐defined oligo(amidoamine)s (OAAs) with either two or six cysteine molecules for binding to the gold surface and either with or without a PEG chain (3400 Da). The presence of the PEG chain considerably increased the hydrodynamic diameter of both dissolved macromolecules and macromolecule‐conjugated gold nanoparticles.